KOMUNIKASI DEVICE-TO-DEVICE PADA JARINGAN SELULER 5G MENGGUNAKAN MMWAVE - Mulyadi, Rasheed Abdurrahman; Usman, Uke Kurniawan (AVITEC, 2020)
This article discusses about device-to-device communication on 5G cellular networks using mmWave. Device-to-device communication will support 5G cellular technology, because it can be a solution to overcome the limitations of cellular coverage and service capacity. D2D can be used in a variety of applications. The main problem in D2D is that interference between signals in one cell will be very vulnerable to occur, so that effective resource management is needed. In addition, the use of D2D will also increase the complexity of a cellular system, in terms of resource management, interference, and also the routing required. Several studies have been carried out to create D2D communication that can be implemented effectively on 5G. One of them is research to perfect the load balancing scheme which is one of the functions obtained from D2D communication. Load balancing is the distribution of cellular traffic loads, using D2D the traffic load is channeled to communication between devices and reduces the burden on the main network.